Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Motivasi Belajar Siswa - Hardian, Mirza; Destiana, Raja Nurul Fitria; Syafina, Syafina (Universitas Indraprasta PGRI Jakarta, 2024)
Low learning motivation in civic education (PPKn) has a negative impact on achieving learning objectives in the classroom. Low motivation also contributes to the development of important life skills, such as problem-solving ability, creativity, and critical thinking. Efforts that teachers can make to provide learning motivation is to use the Problem-Based Learning (PBL) model. This Action Research applied 2 cycles in class VIII. G of SMP Negeri 8 Pekanbaru through stages of activity planning, implementation, monitoring, and reflection. The findings of the research increased learning motivation to 34.13 in cycle 1. The results of cycle II showed a quite significant increase in student learning motivation to 41.66. The improvement in student learning motivation using PBL indicates that learning motivation in class VIII G can be increased by involving students in learning activities. The implementation of PBL can encourage students to find solutions to problems encountered in learning activities, thus making the learning process student-centered.